Relationship Between Nutrition Intake and Outcome After Subarachnoid Hemorrhage: Results From the International Nutritional Survey. (October 2021) - Badjatia, Neeraj; Ryan, Alice; Choi, H. Alex; Parikh, Gunjan Y.; Jiang, Xuran; Day, Andrew G.; Heyland, Daren K.
Background: A previous study suggested an association between low caloric intake(CI), negative nitrogen balance, and poor outcome after subarachnoid hemorrhage(SAH). Objective of this multinational, multicenter study was to investigate whether clinical outcomes vary by protein intake(PI) or CI in SAH patients adjusting for the nutritional risk as judged by the modified NUTrition Risk in the Critically Ill (mNUTRIC) score. Methods: The International Nutrition Survey(INS) 2007-2014 was utilized to describe the characteristics, outcomes and nutrition use. A subgroup of patients from 2013 and 2014(when NUTRIC score was captured) examined the association between CI and PI and time to discharge alive(TTDA) from hospital using Cox regression models, adjusting for nutrition risk classified by the mNUTRIC score as low(0-4) or high(5-9). Results: There were 489 SAH patients(57% female with a mean ± SD age 57.5 ± 13.9 years, BMI of 25.9 ± 5.3 kg/m 2 and APACHE-2 score 19.4 ± 7.0. Majority(85%) received enteral nutrition(EN) only, with a time to initiation of EN of 35.4 ± 35.2 hours. 64% had EN interrupted. Patients received a CI of 14.6 ± 7.1 calories/kg/day and PI 0.7 ± 0.3 grams/kg/day corresponding to 59% and 55% of total prescribed CI and PI respectively. In the 2013 and 2014 subgroup there were 226 SAH patients with a mNUTRIC score of 3.4 ± 1.8. Increased CI and PI were associated with faster TTDA among high mNUTRIC patients(HR per 20% of prescription received = 1.34[95% CI, 1.03 -1.76] for CI and 1.44[1.07 -1.93] for PI), but not low mNUTRIC patients(CI: HR = 0.95[0.77 -1.16] PI:0.95[0.78 -1.16]). Conclusions: Results from this multicenter study found that SAH patients received under 60% of their prescribed CI and PI. Further, achieving greater CI and PI in hi risk SAH patients was associated with improved TTDA. mNUTRIC serves to identify SAH patients that benefit most from artificial nutrition and efforts to optimize protein and caloric delivery in this subpopulation should be maximized.